Nanoengineering the cell surface for targeted drug and cell delivery - Karp, Jeff (Henry Stewart Talks, 2015)
MSCs from discovery to over 450 clinical trials, Current challenges to maximize clinical success, Technologies for controlling cell fate and function following transplantation, mRNA transfection strategy using cells for targeted delivery of biologics, Engineering cells with an intracellular depots of phenotype altering agents, Drug delivery or programming cell fate via intracrine-, paracrine-, and endocrine-like mechanisms, Next generation nanonsensors to study secretome in vivo
Reviewed at 2021/10/11